Major depletion of SOX2+ stem cells in the adult pituitary is not restored which does not affect hormonal cell homeostasis and remodelling. Issue 1 (December 2017) - Roose, Heleen; Cox, Benoit; Boretto, Matteo; Gysemans, Conny; Vennekens, Annelies; Vankelecom, Hugo
Abstract The pituitary gland contains SOX2-expressing stem cells. However, their functional significance remains largely unmapped. We investigated their importance by depleting SOX2+ cells through diphtheria toxin (DT)-mediated ablation. DT treatment of adult Sox2CreERT2/+ ;R26iDTR/+ mice (after tamoxifen-induced expression of DT receptor in SOX2+ cells) resulted in 80% obliteration of SOX2+ cells in the endocrine pituitary, coinciding with reduced pituisphere-forming activity. Counterintuitively for a stem cell population, the SOX2+ cell compartment did not repopulate. Considering the more active phenotype of the stem cells during early-postnatal pituitary maturation, SOX2+ cell ablation was also performed in 4- and 1-week-old animals. Ablation grade diminished with decreasing age and was accompanied by a proliferative reaction of the SOX2+ cells, suggesting a rescue attempt. Despite this activation, SOX2+ cells did also not recover. Finally, the major SOX2+ cell depletion in adult mice did not affect the homeostatic maintenance of pituitary hormonal cell populations, nor the corticotrope remodelling response to adrenalectomy challenge. Taken together, our study shows that pituitary SOX2+ fail to regenerate after major depletion which does not affect adult endocrine cell homeostasis and remodelling. Thus, pituitary SOX2+ cells may constitute a copious stem cell reserve or may have other critical role(s) still to be clearly defined.